Interpreting clinical trial results by deductive reasoning: In search of improved trial design. (11th September 2017) - Kurbel, Sven; Mihaljević, Slobodan
Abstract : Clinical trial results are often interpreted by inductive reasoning, in a trial design‐limited manner, directed toward modifications of the current clinical practice. Deductive reasoning is an alternative in which results of relevant trials are combined in indisputable premises that lead to a conclusion easily testable in future trials.